Bilateral ureterohydronephrosis after intestinal pseudo-obstruction in a patient with systemic lupus erythematosus - Qi, Wanting; Zhou, Yangzhong; Zhao, Jiuliang (Rheumatology and immunology research, 2022)
Conflict of Interest Jiuliang Zhao is an Editorial Board Member of the journal. The article was subject to the journal’s standard procedures, with peer review handled independently of the editor and his research groups. Clinical Features, Morbidity, and Risk Factors of Intestinal Pseudo-obstruction in Systemic Lupus Erythematosus: A Retrospective Case-control Study.